Behavioral health disability innovations in prevention and management - Warren, Pamela A.; SpringerLink (Online service). (New York London Springer, 2010)
Behavioral Health Disability Innovations in Prevention and Management Pamela A. Warren It's a frequent occurrence: a sick worker is treated for physical symptoms, but receives little care for the accompanying psychological problems. The employee is put on ineffective medication, is suspected of malingering, and never fully recovers. The authors of the Behavioral Health Disability attribute this no-win situation to systemic misunderstandings between medical and mental health providers, employers, and insurers?often despite earnest efforts toward integrative care. In its place, they set out a practical, evidence-based framework not only for more accurate evaluation and more effective treatment of conditions, but also better collaboration across specialties, with the legal and insurance systems, and with the workplace, resulting in fewer mental health disability claims, fewer ?maintenance? prescriptions, lower costs, and ultimately better outcomes for clients. This book: Represents the viewpoints of multiple treating professionals?primary care, occupational medicine, psychology, psychiatry, and rehabilitation medicine as well as legal, employer, and insurer perspectives. Identifies strengths and weaknesses in standard assessment, treatment, or policy for each specialty. Examines referral, documentation, and compliance issues. Describes the medicalization of psychosocial concerns, and how it can be avoided. Includes strategies for addressing the individual's return to work. Offers recommendations for immediate and long-term improvements in disability case management. The Behavioral Health Disability provides groundbreaking guidance for the spectrum of professionals involved in psychiatric disability cases, among them health and clinical psychologists, psychiatrists, primary care physicians and rehabilitation specialists, clinical social workers, nurses, and insurance companies.
A critique of the behavioral health disability system -- Prevalence of behavioral health concerns and systemic issues in disability treatment and management -- Effective psychological evaluation and management of behavioral health concerns -- Assessment of psychosocial contributions to disability -- Psychiatric issues in behavioral health disability -- The occupational medicine perspective on behavioral health concerns -- Physical therapy treatment and the impact of behavioral health concerns -- Vocational rehabilitation considerations for mental health impairments in the workplace -- Case management and behavioral health disability -- Behavioral health and disability insurance: a perspective -- The legal system and behavioral health.
Electronic reproduction.
Keywords: Mental illness -- Treatment; People with mental disabilities -- Services for; Mental health services; Evidence-based medicine; Mental disorders -- Prevention & control; Mental disorders -- Therapy; Mentally ill Persons; Electronic books